The use of technology in the assessment and monitorization of a season in a professional padel player: A case study - Carnero-Diaz, A.; Pecci, J.; Reverte-Pagola, G.; Da Silva-Grigoletto, M. E. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
Training process in elite padel players is influenced by travels and competitions density. The irregularity in the workloads, as well as demands of the season, could affect the musculoskeletal structures. Strength training has a protective role against the injury incidence, but the competitive context does not always allow adequate periodization of training and thus achieve adaptations. The aim of this study is to analyze, using technological tools, if improvements in player`s fitness are accompanied by improvements in sport performance through a case study. An elite padel player was analyzed during the 2021 season. Physical fitness was evaluated using different technological tools. Athlete monitoring was carried out using self-reported forms and sport performance was assessed through the results obtained in the World Padel Tour ranking at the end of the season. During the training process, multidimensional training was carried out in order to achieve the maximum availability of specific loads through coadjuvant training. Results of the assessment show slight improvements in all fitness tests. Assessment of sport performance reports an increased number of victories and a better position in the professional ranking. Musculoskeletal improvements helped the athlete`s workload tolerance, allowing overall improvement in padel performance. The training approach from this study has shown to be effective in maintaining or even improving force-producing capacity in lower and upper limbs, force-velocity relationship, agility and sport performance, despite the high competitive density. This work provides coaches with a practical approach to assess, monitor and design a competitive season for an elite padel player.